Parasitological study of mountain viscacha fecal pellets from patagonia over the last 1200 years (‘Cueva Peligro’, Chubut province, Argentina) - Beltrame, María Ornela (2019)
The aim of the present study was to examine the parasite fauna present in mountain viscacha Lagidium viscacia (Caviomorpha, Chinchillidae) fecal pellets collected from 'Cueva Peligro', a cave located in Chubut province, Patagonia, Argentina, throughout the last 1200 years. A total of 84 samples were examined for parasites. Each pellet was whole processed: rehydrated, homogenized, sediment and examined using light microscopy. The samples and eggs of parasites present were described, measured and photographed. Thirty-eight samples tested positive for the nematodes Heteroxynema (Cavioxyura) viscaciae Sutton & Hugot, 1989, Helminthoxys effilatus Schuurmans-Stekhoven, 1951 (Oxyurida: Oxyuridae), Trichuris sp. Roederer, 1761 (Trichinellida: Trichuridae) and one anoplocephalid species (Cestoda: Anoplocephalidae). This is the first time that H. effilatus is reported from ancient times. Significant differences of parasite occurrences through this temporal period were recorded. Parasitic life cycles and their presence along the studied period are so discussed.